Simulation of Seismic Wave Scattering by Embedded Cavities in an Elastic Half-Plane Using the Novel Singular Boundary Method (Advances in Applied Mathematics and Mechanics, 2018)
In the present study, a numerical procedure for analyzing the seismic response of the linear elastic half-plane including buried cavities subjected to incident P and SV waves is proposed by means of the novel singular boundary method (SBM). The SBM is a recently developed boundary-type meshless collocation method, which applies the singular fundamental solutions as basis functions. In order to avoid the singularities of the fundamental solutions, the SBM introduces the concept of origin intensity factors at the origin. With the aid of the origin intensity factors of the Laplace and the plane-strain elastostatic problems, this study first derives the origin intensity factors for the traction boundary condition as well as the origin intensity factors for the flat boundary, in order to form the SBM formulation for wave scattering problems in the linear elastic half-plane including buried cavities. Results obtained with the SBM model are compared with the results obtained with the finite element method, which shows that the method is quite promising for studying seismic wave scattering problems.